Proceedings of the Thirtieth Annual Symposium on Computational Geometry 2014
DOI: 10.1145/2582112.2582145
|View full text |Cite
|
Sign up to set email alerts
|

Counting and Enumerating Crossing-free Geometric Graphs

Abstract: We describe a framework for counting and enumerating various types of crossing-free geometric graphs on a planar point set. The framework generalizes ideas of Alvarez and Seidel, who used them to count triangulations in time O(2 n n 2 ) where n is the number of points. The main idea is to reduce the problem of counting geometric graphs to counting source-sink paths in a directed acyclic graph.The following new results will emerge more or less directly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…At a different level of complexity, the idea of working ahead occurs in an algorithm of Wettstein [9,Section 6]. This trick, credited to Emo Welzl, is used to achieve polynomial delay between successive solutions when enumerating non-crossing perfect matching of a planar point set, despite having to build up a network with exponential space in a preprocessing phase.…”
Section: Working Aheadmentioning
confidence: 99%
“…At a different level of complexity, the idea of working ahead occurs in an algorithm of Wettstein [9,Section 6]. This trick, credited to Emo Welzl, is used to achieve polynomial delay between successive solutions when enumerating non-crossing perfect matching of a planar point set, despite having to build up a network with exponential space in a preprocessing phase.…”
Section: Working Aheadmentioning
confidence: 99%
“…It is a challenging problem to determine the number of configurations faster than listing all such configurations (i.e., count faster than enumerate) [3]. Exponential-time algorithms have been developed for triangulations [4], planar graphs [22], and matchings [28] that count these structures exponentially faster than the number of structures. Recently, it has been shown that the number of triangulations on n points in the plane can be counted in subexponential time [19], and this result extends to counting noncrossing prefect matchings, spanning trees, spanning cycles, 3-regular graphs, and more.…”
Section: Counting Algorithmmentioning
confidence: 99%
“…Although there has been significant research on counting non-crossing configurations in the plane, including matchings, simple polygons, spanning trees, triangulations, and pseudotriangulations, the complexity of these problems has remained undetermined. Research on these problems has instead focused on determining the number of configurations for special classes of point sets [20,8,24], bounding the number of configurations as a function of the number of points [2,4,39,37,17,38,1,33,3,36,21,10], developing exponential-or subexponential-time counting algorithms [12,7,42,5,30,13], or finding faster approximations [6,27].…”
Section: Introductionmentioning
confidence: 99%